2008
DOI: 10.1097/pgp.0b013e31815d060d
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor Receptor Expression in Serous Ovarian Carcinoma: An Immunohistochemical Study With Galectin-3 and Cyclin D1 and Outcome

Abstract: This study investigated the expression of epidermal growth factor receptor (EGFR), galectin-3 and cyclin D1 in a cohort of ovarian serous carcinomas with regard to outcome and clinicopathologic parameters. Formalin-fixed paraffin-embedded archival tissues of fifty ovarian serous carcinomas were stained with anti-bodies to EGFR, Gal-3, and cyclin D1 by automated immunohistochemistry. Additionally, 10 benign serous cystadenomas and 10 typical serous borderline ovarian tumors were included in the study. Immunosta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 33 publications
4
46
0
Order By: Relevance
“…These findings suggest that Gal-3 expression can be a prognostic factor for PFS and may play a role in regulating the response to paclitaxel-based chemotherapy in the treatment of EOC. Our results on the association between high Gal-3 expression and poor survival in EOCs are in agreement with a previous study [17]. Brustmann reported that Gal-3 immunostaining of any pattern (nuclear and cytoplasmic as well as only cytoplasmic) was not related to grade or stage in cancers; only cytoplasmic expression was associated with poor outcome [17].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…These findings suggest that Gal-3 expression can be a prognostic factor for PFS and may play a role in regulating the response to paclitaxel-based chemotherapy in the treatment of EOC. Our results on the association between high Gal-3 expression and poor survival in EOCs are in agreement with a previous study [17]. Brustmann reported that Gal-3 immunostaining of any pattern (nuclear and cytoplasmic as well as only cytoplasmic) was not related to grade or stage in cancers; only cytoplasmic expression was associated with poor outcome [17].…”
Section: Discussionsupporting
confidence: 94%
“…One study reported Gal-3 downregulation in EOC compared to normal tissue and no correlation between expression and clinicopathological features [16]. Another report suggested that cytoplasmic staining was associated with poorer outcome compared to nuclear staining [17]. The functional significance of Gal-3 overexpression in EOC is not yet known.…”
Section: Introductionmentioning
confidence: 96%
“…In digestive system, higher levels of galectin-3 were reported in colon (Arfaoui-Toumi et al 2010), stomach (Okada et al 2006) and liver cancer (Matsuda et al 2008). Galectin-3 has also been detected overexpressed in other tumors (Chiu et al 2010;Szöke et al 2007;Righi et al 2010;Sakaki et al 2010;Abdou et al 2010;Koo and Jung 2011;Choi et al 2010;SaVar et al 2011;Brustmann 2008;Canesin et al 2010). The mechanisms by which galectin-3 brings into its eVects largely remain unknown.…”
Section: Discussionmentioning
confidence: 93%
“…For EGFR, 15 studies in 2471 patients were included in the metaanalysis (Supplementary Table 4; median study size 106 patients, range 40 -783; Kaufmann et al, 1995;Scambia et al, 1995;Bartlett et al, 1996;Fischer-Colbrie et al, 1997;Skirnisdottir et al, 2001b;Elie et al, 2004;Nielsen et al, 2004;Psyrri et al, 2005;Raspollini et al, 2005;Schilder et al, 2005;Wang et al, 2005;Castellvi et al, 2006;Lassus et al, 2006;Brustmann, 2008;de Graeff et al, 2008). Again, all studies were classified as phase II biomarker studies.…”
Section: Study Characteristicsmentioning
confidence: 99%